Implementation of the Mobile Court Policy in Religious Courts On The Legal Political Perspective - Hazar Kusmayanti, Hazar; Madiha Dzakiyyah Chairunnisa, Madiha Dzakiyyah Chairunnisa; Dede Kania, Dede Kania; Rajamanickam, Ramalinggam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The mobile court policy is a way in which the court can provide the best and equal service to justice seekers by the principles of simplicity, speed and low costs. This research discusses the mobile court policy and its implementation in religious courts from a legal-political perspective. The research method uses empirical juridical. Interviews were conducted with judges and litigants in mobile courts at three Religious Courts, i.e.: Tasikmalaya, Soreang and Subang. Document studies are used to search for regulations and related case documents. The research findings show that the problems with implementing mobile courts in the three religious courts are: the infrastructure for mobile courts is still inadequate because they are held outside the building and far from the Religious Courts; public education is still low, they do not even have an understanding of the law and the judicial process; the judge also acts as a mediator in the mobile court and; case settlement was only carried out twice. This condition is increasingly problematic because most cases are divorces, so the facts in the trial are less accurate and affect the quality of court decisions. An interesting finding is that the mobile court is an effort to provide access to justice for people in unreachable areas by the Religious Courts and as a solution to reduce the divorce rate. However, in fact it increases the divorce rate in the target area. People think that the mobile court makes it easier for them to decide on divorce.